2014
DOI: 10.1016/j.mehy.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplant with gene therapy for Friedreich ataxia

Abstract: We advance the overarching hypothesis that stem cell therapy is a potent treatment for Friedreich’s ataxia (FRDA). Here, we discuss the feasibility of autologous transplantation in FRDA, highlighting the need for the successful isolation of the FRDA patient’s bone marrow-derived mesenchymal stem cells, followed by characterization that these cells maintain the GAA repeat expansion and the reduced FXN mRNA expression, both hallmark features of FRDA. Next, we discuss the need for assessment of the proliferative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The other case continues to school and her life with various self-care skills. As Tajiri et al showed in MSC transplanted patients, differentiation into peripheral neurons and cardiomyocytes with their proliferative and pluripotency properties [11], MSCs constitute the leading cause of FA's death, myocardial fibrosis, cardiac failure, and neurodegeneration [12]. This suggests MSC could be effective in slowing down these pathologies with the combination of and clinical findings.…”
Section: Discussionmentioning
confidence: 99%
“…The other case continues to school and her life with various self-care skills. As Tajiri et al showed in MSC transplanted patients, differentiation into peripheral neurons and cardiomyocytes with their proliferative and pluripotency properties [11], MSCs constitute the leading cause of FA's death, myocardial fibrosis, cardiac failure, and neurodegeneration [12]. This suggests MSC could be effective in slowing down these pathologies with the combination of and clinical findings.…”
Section: Discussionmentioning
confidence: 99%
“…Friedreich ataxia (FRDA) caused by genetic abnormalities in the FXN gene is an autosomal recessive disorder (47). Researchers who reported that the HSPC transplantation can be used for the treatment of FRDA carried out a study based on the gene correction on CD34+ cells from a patient's peripheral blood with FRDA by using CRISPR/Cas9 system.…”
Section: Basic Research On Crispr System In Hematopoieticmentioning
confidence: 99%
“…Stem cell therapies for neurologic disease have had suggested mechanisms that range from neural replacement to nerve growth factor enhancement to use as a delivery vehicle for other therapy [40][41][42]. A phase 1/2a open-label study of intravenous adipose-derived mesenchymal stem cell treatment in 6 patients with spinocerebellar ataxia type 3 (ClinicalTrials.gov Identifier: NCT01649687) demonstrated good safety and tolerability over 1 year with plans to conduct a larger, controlled trial in the future [43].…”
Section: Neural Replacementmentioning
confidence: 99%